The Development of Environment-Based Audio-Visual Teaching Materials in Science and Social Learning - Lidvina Pasu, Maria; Yuliana Pasu, Maria; Gelu, Afrianus; Mahendra Dinatha, Ngurah (Jurnal Educative: Journal of Educational Studies, 2024)
The lack of teacher creativity in creating enjoyable learning means that students do not participate fully in the learning process because they only use lecture approaches and printed books as learning resources. One of the new innovations in this research is producing learning resources in the form of environment-based audio-visual teaching materials. The research and development (R&D) approach used in this research uses a 3D development model starting from define, design and develop. 10 grade IV students participated in research conducted at SDK Majamere. Media experts and material experts carried out data analysis. The information collected consists of quantitative data from expert validation results, teacher and student questionnaire responses, as well as qualitative data from assessor recommendations and comments. The validated presentation obtained a percentage of 88% from material experts, 82% from media experts, and 85% from language experts. The student questionnaire response was 82%, while the teacher response was 83% and 81%. The research conclusion shows that the environment-based audio visual teaching materials developed have a very suitable level of validation so they are good for use in class IV in elementary school science and social subjects AbstrakKurangnya kreativitas guru dalam menciptakan pembelajaran yang menyenangkan membuat siswa tidak berpartisipasi penuh dalam proses pembelajaran, karena hanya menggunakan pendekatan ceramah dan buku cetak sebagai sumber belajar. Salah satu inovasi baru dalam penelitian ini adalah menghasilkan sumber belajar berupa bahan ajar audio visual berbasis lingkungan. Pendekatan penelitian dan pengembangan (R&D) yang digunakan dalam penelitian ini menggunakan model pengembangan 3D yang dimulai dari pendefinisian (define), perancangan (design), dan pengembangan (develop). Sebanyak 10 siswa kelas IV berpartisipasi dalam penelitian yang dilakukan di SDK Majamere. Ahli media dan ahli materi melakukan analisis data. Informasi yang dikumpulkan terdiri dari data kuantitatif dari hasil validasi ahli, respon kuesioner guru dan siswa, serta data kualitatif dari rekomendasi dan komentar penilai. Presentasi yang divalidasi memperoleh persentase 88% dari ahli materi, 82% dari ahli media, dan 85% dari ahli bahasa. Respon kuesioner siswa sebesar 82%, sedangkan respon guru sebesar 83% dan 81%. Kesimpulan penelitian menunjukkan bahwa bahan ajar audio visual berbasis lingkungan yang dikembangkan memiliki tingkat validasi yang sangat layak sehingga baik untuk digunakan di kelas IV pada mata pelajaran Ilmu Pengetahuan Alam dan IPS sekolah dasar.